1976
DOI: 10.1007/bf02003781
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone in human saliva

Abstract: Testosterone has been detected in whole human saliva. Levels averaged (+/- SE) 295 +/- 36 and 195 +/- 25 pg/ml in adult males and females, respectively, and usually were undetectable in children. In adult males, the excretion of testosterone in saliva appeared to follow a circadian rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

1977
1977
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 14 publications
3
33
1
Order By: Relevance
“…Sugar-free gum (Vivident Xylit ® ) was used to increase saliva flow (27). Since, in adult males, the excretion of testosterone in saliva appears to follow a circadian rhythm (28) and be a pulsatile secretion (29), four samples were collected at intervals of 30 min between 9:00 and 12:00 a.m. Saliva was assayed using diagnostic kits (diagnostic Systems laboratories inc., uSa) and modified radioimmunoassay methods (30). Testosterone assay sensitivity was 0.3 pg/ml with intra-and inter-assay coefficients of variation of <9.2% and <8.3%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Sugar-free gum (Vivident Xylit ® ) was used to increase saliva flow (27). Since, in adult males, the excretion of testosterone in saliva appears to follow a circadian rhythm (28) and be a pulsatile secretion (29), four samples were collected at intervals of 30 min between 9:00 and 12:00 a.m. Saliva was assayed using diagnostic kits (diagnostic Systems laboratories inc., uSa) and modified radioimmunoassay methods (30). Testosterone assay sensitivity was 0.3 pg/ml with intra-and inter-assay coefficients of variation of <9.2% and <8.3%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Chaussain et al (1978) observed the variations in serum TeBG binding capacity in infants during the first year of life, suggesting that the increased T observed in boys in the first months of life may be a passive phenomenon, secondary to an increase in the serum level of TeBG. Recently, T in saliva appear to reflect the non-protein bound T in the blood and provide useful information about the biologically available androgen without the possible stressful effects of venipuncture and the use of the complicated techniques (Landman et al, 1976;Luisi et al, 1980;Wang et al, 1981;Baxendale et al, 1982). Thus measurement of ST in this period may definetely settle this point.…”
Section: ) St Concentrationmentioning
confidence: 99%
“…In addition, the circadian rhythm of the ST concentration (Landman et al, 1976) and the inverse relation between the flow rate of parotid fluid and the steroid concentration (Katz and Shannon, 1969), which may affect the accuracy of ST concentration, were reported. Therefore, in this study, all saliva samples were obtained without stimulation at a definite time between 1400 and 1600 h to obtain accurate information.…”
Section: ) St Concentrationmentioning
confidence: 99%
“…A normal man has about one hundred-thousandth gram of hormone per liter of blood (i.e., ten nanograms/milliliter); women have roughly one-seventh as much. Soon it was practical to measure free T (i.e., T not bound to protein, which is assumed to be the physiologically active portion; in saliva with a concentration of about one-hundredth that of total T in blood (Landman et al 1976;Wang et al 1981;Riad-Fahmy et al 1982;. Collection of saliva rather than blood has made studies on humans more practical.…”
Section: A Primer On Testosteronementioning
confidence: 99%